Further SAR on the (Phenylsulfonyl)piperazine Scaffold as Inhibitors of the Aedes aegypti Kir1 (AeKir) Channel and Larvicides. (28th October 2020) - Aretz, Christopher D.; Kharade, Sujay V.; Chronister, Keagan; Rusconi Trigueros, Renata; Martinez Rodriguez, Erick J.; Piermarini, Peter M.; Denton, Jerod S.; Hopkins, Corey R.
Abstract: Zika virus (ZIKV), dengue fever (DENV) and chikungunya (CHIKV) are arboviruses that are spread to humans from the bite of an infected adult female Aedes aegypti mosquito. As there are no effective vaccines or therapeutics for these diseases, the primary strategy for controlling the spread of these viruses is to prevent the mosquito from biting humans through the use of insecticides. Unfortunately, the commonly used classes of insecticides have seen a significant increase in resistance, thus complicating control efforts. Inhibiting the renal inward rectifier potassium (Kir) channel of the mosquito vector Aedes aegypti has been shown to be a promising target for the development of novel mosquitocides. We have shown that Kir1 channels play key roles in mosquito diuresis, hemolymph potassium homeostasis, flight, and reproduction. Previous work from our laboratories identified a novel (phenylsulfonyl)piperazine scaffold as potent Ae Kir channel inhibitors with activity against both adult and larval mosquitoes. Herein, we report further SAR work around this scaffold and have identified additional compounds with improved in vitro potency and mosquito larvae toxicity. Abstract : Mosquito killers : A series of five‐membered heterocyclic analogs were designed, synthesized and biologically evaluated against the Aedes aegypti Kir channel. The compounds were found to be potent inhibitors of the ion channel at nanomolar concentrations. Additionally, select compounds were shown to be toxic to multiple strains of Aedes aegypti larvae at 48 h.